Historic landscape characterisation (HLC) and the Belvedere Project: a comparison through the lens of a Steinitz’s framework for Geodesign - Laura Beatriz Lage (Disegnare con)
This present essay aims to discuss two methodologies related to spatial plans – Historic Landscape Characterisation (HLC) and the Belvedere Project - under the lens of a framework for Geodesign developed by Carl Steinitz. Geodesign, according to Steinitz (2012: preface) “is the process of changing geography by design”. This process is closely related to spatial planning, looking to the future. But, in order to do so, it is necessary a previous understanding of the place to be intervened as well as involve different disciplines and stakeholders for a better decision-making. Both methodologies provide a deep understanding of the place and encourage future development in line with the preservation of the past, that is, managing change in current landscapes attempting to maintain their main characteristics, identities and qualities, using them as inspiration for the future. DOI: https://doi.org/10.20365/disegnarecon.20.2018.9